2022
DOI: 10.3390/app12052593
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Behavior and Impact on Driving Safety of Spalling Blocks Comprising High-Speed-Railway Tunnel Lining

Abstract: The lining of operating high-speed-railway tunnels suffers from cracks, the peeling of material, and other deteriorations and defects, all of which seriously affect driving safety. However, the trajectory of a falling block from the tunnel lining in a tunnel train wind environment and its impact on driving safety are unknown. To study the movement of falling blocks under a coupling effect of tunnel train wind and the local flow field of the falling blocks, a three-dimensional gas–solid-coupling numerical calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A high-speed train passing through a tunnel will produce aerodynamic effects and bring an additional load to the lining structure. In addition, under the long-term cyclic action of the aerodynamic effects, fatigue damage to the concrete will occur, which will affect the safety of the lining structure [28]. Wang et al [29] found that under the cyclic dynamic load of a high-speed train, micro-cracks in the concrete will further expand.…”
Section: Introductionmentioning
confidence: 99%
“…A high-speed train passing through a tunnel will produce aerodynamic effects and bring an additional load to the lining structure. In addition, under the long-term cyclic action of the aerodynamic effects, fatigue damage to the concrete will occur, which will affect the safety of the lining structure [28]. Wang et al [29] found that under the cyclic dynamic load of a high-speed train, micro-cracks in the concrete will further expand.…”
Section: Introductionmentioning
confidence: 99%
“…It affects the crack initiation and propagation in the structure [1]; causes high-cycle fatigue damage to train structures [2,3], tunnel structures [4][5][6], and pressure-bearing tunnel facilities (including fire doors, control boxes, signal lights, etc.) [3,7,8]; and leads to vibration discomfort for passengers [9], threatening the safety of transportation systems [10,11]. For example, in 1999, influenced by long-term aerodynamic loads, a block of lining detached from the Rebunhama high-speed railway tunnel in Japan, which caused train derailment and the cancellation of 51 subsequent trains [1,12].…”
Section: Introductionmentioning
confidence: 99%